2021
DOI: 10.3389/fphar.2021.613105
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Interleukin-1β in Glycinergic Transmission at the Central Amygdala

Abstract: Interleukin-1β (IL-1β) is an important cytokine that modulates peripheral and central pain sensitization at the spinal level. Among its effects, it increases spinal cord excitability by reducing inhibitory Glycinergic and GABAergic neurotransmission. In the brain, IL-1β is released by glial cells in regions associated with pain processing during neuropathic pain. It also has important roles in neuroinflammation and in regulating NMDA receptor activity required for learning and memory. The modulation of glycine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…In a previous study, we reported that in CeA neurons, IL-1β induces a short-lasting increment in glycinergic currents five minutes after the addition of IL-1β. However, fifteen minutes later, the whole range of amplitudes diminished, suggesting that IL-1β disaggregates the GlyR clusters and induces endocytosis [22]. Here, in slices from CCI animals, we observed that IL-1β reduces the whole range of current amplitudes, and the bimodality is almost lost, with a shift of the peak amplitudes from the bimodal "2 peaks" at 9pA and 28pA, to 11 pA at 5 min and 14 pA, after 15 min of IL-1β incubation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a previous study, we reported that in CeA neurons, IL-1β induces a short-lasting increment in glycinergic currents five minutes after the addition of IL-1β. However, fifteen minutes later, the whole range of amplitudes diminished, suggesting that IL-1β disaggregates the GlyR clusters and induces endocytosis [22]. Here, in slices from CCI animals, we observed that IL-1β reduces the whole range of current amplitudes, and the bimodality is almost lost, with a shift of the peak amplitudes from the bimodal "2 peaks" at 9pA and 28pA, to 11 pA at 5 min and 14 pA, after 15 min of IL-1β incubation.…”
Section: Discussionmentioning
confidence: 99%
“…We recently reported that spontaneous glycinergic currents in CeA slices are modulated by IL-1β [22]. The described dual effect of IL-1β first increases glycinergic current amplitude by affecting GlyR channel opening and then reduces the amplitudes by disaggregating glycinergic clusters.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Interestingly, IL-1β is involved in the inflammatory response to chronic prostatitis and mediation of pain development. It increases spinal excitability and modulated pain sensitivity at the spinal cord level [ 114 115 ]. In addition, spinal astrocytes produce IL-1β, which activates astrocytes by binding to the IL-1 receptor (IL-1R), contributing to central sensitization and leading to long-term maintenance of chronic pain [ 116 ].…”
Section: Nerve-related Substances In Cp/cppsmentioning
confidence: 99%
“…Diminished synaptic inhibition has been reported as a critical element in rodent models of chronic inflammatory or neuropathic pain (Coull et al 2003 ). The cytokine IL-1β was shown to reduce GABAergic and glycinergic transmission in CNS neurons (Solorza et al 2021 ). Thus, restoration of lost inhibitory signaling in chronic pain would be a promising therapeutic approach.…”
Section: Role Of Inhibitory Transmission In Pain Modulationmentioning
confidence: 99%